2020
DOI: 10.1051/shsconf/20207701004
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Programming Learning Platform: Architecture and Challenges

Abstract: With the rapid development of information technology, programming has become a vital skill. An online judge system can be used as a programming education platform, where the daily activities of users and judges are used to generate useful learning objects (e.g., tasks, solution codes, evaluations). Intelligent software agents can utilize such objects to create an ecosystem. To implement such an ecosystem, a generic architecture that covers the whole lifecycle of data on the platform and the functionalities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
0
7
0
2
Order By: Relevance
“…As a result of the analysis, it was revealed that there is an invariant set of educational tools for any training (Kidd, 2020;Liu et al, 2020;Piteira et al, 2018;Smyk et al, 2020;Watanobe et al, 2020). Their usage has a fairly long history, plus over the past year, a large number of educational platforms and applications have been developed that can be applied or adapted to the educational process.…”
Section: Problem Statementmentioning
confidence: 99%
“…As a result of the analysis, it was revealed that there is an invariant set of educational tools for any training (Kidd, 2020;Liu et al, 2020;Piteira et al, 2018;Smyk et al, 2020;Watanobe et al, 2020). Their usage has a fairly long history, plus over the past year, a large number of educational platforms and applications have been developed that can be applied or adapted to the educational process.…”
Section: Problem Statementmentioning
confidence: 99%
“…All the problems are systematically categorized [54]. The AOJ's resources have been used for various research and application purposes [55] [56]. Recently, AOJ's dataset has been used in the IBM CodeNet Project [57].…”
Section: A Aizu Online Judge Systemmentioning
confidence: 99%
“…Rahman et al (2020) proposed a sequential language model that uses an attention-mechanism-based LSTM neural network to assess and classify source code based on the estimated error probability. Other research activities and challenges which take advantage of OJ system to organise a learning ecosystem have been proposed in Watanobe et al (2020).…”
Section: Related Researchmentioning
confidence: 99%